Gambaran Tingkat Pengetahuan Tentang Basic Life Support Pada Pegawai Non Medis di Lingkungan Fakultas Kedokteran Universitas Pattimura Tahun 2023 - Syemuel Galen Rolanxy Sekerony; Ony W. Angkejaya; Ronald R. Hehanussa (Journal on Education, 2023)
According to the World Health Organization (WHO) data in 2005, there were 57.03 million deaths worldwide. Cardiac arrest remains a major problem, with the global incidence rate of cardiac arrest being around 37% in 2012 and increasing to 43% in 2016. There are not many laypeople who have received training in cardiopulmonary resuscitation (CPR), so the chances of saving the lives of patients with cardiac arrest are likely to be low. This study is a descriptive study using primary data with a cross-sectional approach. The results of the study showed that the most common level of knowledge was a lack of knowledge, with 49 people (77.8%) falling into this category. Based on age categories, the largest group was early adults, with 45 people (71.4%) falling into this category. Based on gender, the largest group was females, with 40 people (63.5%) falling into this category. Based on the highest level of education, the largest group was university graduates, with 43 people (68.3%) falling into this category. Additionally, 59 people (93.7%) reported having previously attended CPR training.